Synthesis and Preliminary Inhibition Study of Carbonyl Thiourea Derivatives on Corrosion of Mild Steel in Acidic Media - Siti Najihah Md Hashim; Karimah Kassim; Juliana Jumal (AENSI Publisher, 2024)
Non-Indexed Publication